Wow assingi gen. and spec. n., with description of a new tribe of Aleocharinae (Coleoptera, Staphylinidae) - Jałoszyński, Paweł; Maruyama, Munetoshi; Klimaszewski, Jan (Zootaxa, 2023)
A new tribe, Wowini Jałoszyński, Maruyama & Klimaszewski, trib. n., based on a new genus, Wow Jałoszyński, Maruyama & Klimaszewski, gen. n., is established to accommodate an extraordinary new species of aleocharine rove beetles, Wow assingi Jałoszyński, Maruyama & Klimaszewski, spec. n. The species was recently discovered in Yunnan, China. It shows a set of characters unknown in this combination in any other nominal taxon of Aleocharinae. The external morphology and genital male structures are illustrated and discussed. A possible close relationship of the new tribe with Oxypodinini Fenyes is proposed as a working hypothesis, and a parallel evolution of unusual cephalic transformations between Wowini and Keratodegnathus Pace (Lomechusini) is discussed.